Chapter The Pursuit of Happiness: a Reflection on the Calling Construct - Barbieri, Barbara (Studies on Adult Learning and Education, 2018)
This brief chapter arises from reflections on the research studies relating to the Calling construct, carry out by colleagues from the University of Padua. Basically this is a reasoning on the implications of which we should (as academics) always keep in mind when we are called to think about career paths for students, and how it could be important to help students to develop a Calling, putting them in the conditions of making an aware and passionate choice about their future working life.